Selective excitation in transparent oxyfluoride glass-ceramics doped with Nd3+. Issue 4 (April 2017) - Gorni, G.; Velázquez, J.J.; Mather, G.C.; Durán, A.; Chen, G.; Sundararajan, M.; Balda, R.; Fernández, J.; Pascual, M.J.
Abstract: Transparent oxyfluoride nano-glass-ceramics have been prepared by melting-quenching and doped with five different Nd 3+ concentrations (0.1–2 mol%) to obtain the most efficient 4 F3/2  →  4 I11/2, 13/2 emission. It was observed by differential thermal analysis (DTA) that the addition of Nd 3+ does not affect the crystallization mechanism which corresponds to a diffusion-controlled volumetric process that starts from a constant number of nuclei. Nevertheless, the presence of the dopant affects the kinetics due to the progressive increase of Tg on increasing the Nd 3+ content. LaF3 crystals with a size between 9 and 12 nm are obtained after heat treatments at Tg  + 20–80 °C as confirmed by X-ray diffraction (XRD) and high resolution transmission electron microscopy (HR-TEM). Energy dispersive X-ray (EDX) analysis shows the incorporation of Nd 3+ ions into the LaF3 nano-crystals. Judd-Ofelt analysis from the absorption spectra further demonstrate the incorporation of Nd 3+ ions into the fluoride phase and the most relevant parameters such as radiative lifetime and stimulated emission cross-section are calculated. A detailed optical characterisation clearly shows that Nd 3+ ions in the glass-ceramics are incorporated in both crystalline and amorphous phases. Low temperature site-selective emission and excitation spectra, together with the different lifetime values of the 4 F3/2 state depending on the excitation and emission wavelengths, allow emission from Nd 3+ ions in the LaF3 nanocrystals to be identified and correlated with the structural properties. As the Nd 3+ concentration is increased beyond 0.1 mol%, a stronger quenching of lifetime is observed for Nd 3+ ions residing in LaF3 crystals than for those dispersed in the glass matrix. This strong concentration quenching is explained by the much higher concentration of Nd 3+ ions in the crystalline phase with respect to that in the glass matrix.